(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Studies were carried out on the preparation of powerful phenyl from petuli (Trewia nudiflora linn) seed oil. It was found that petuli seed contains 22 % of pale-yellow coloured oil. The physical and chemical characteristics of the oil were determined by the conventional methods and the fatty acid by gas liquid chromatography (G.L.C). From the results it is evident that the oil can be used suitably for the preparation of powerful phenyl on accounts of its high α-elaeostearic acid (38 %) a major fatty acid component content and higher saponification value (185). This phenyl was applied on bacteria and found effective result. Bangladesh J. Sci. Ind. Res. 41(3-4), 203-206, 2006